The airway epithelium is a direct source of matrix degrading enzymes in bronchiolitis obliterans syndrome - Banerjee, B.; Ling, K.; Sutanto, E.; Musk, M.; Yerkovich, S.; Hopkins, P.; Stick, S.; Kicic, Anthony; Chambers, D. (2011)
Background: Long-term survival after lung transplantation is hindered by the development of bronchiolitis obliterans syndrome (BOS), and recent evidence suggests that dysregulated epithelial repair may underlie its development. Because matrix metalloproteinase (MMP) -2 and MMP-9 secretion is integral to repair, we hypothesized that airway epithelial cells from patients with BOS would over-express these matrix-degrading enzymes. Methods: Cells obtained from bronchial and bronchiolar brushings from patients with and without BOS (without acute rejection or infection) were analyzed via quantitative polymerase chain reaction and immunocytochemistry for MMP-2, and MMP-9 gene and protein expression. The expression of tissue inhibitor of metalloproteinase (TIMP)2 and TIMP1 was also assessed. MMP activity in bronchoalveolar lavage was determined via gelatin zymography. Results: MMP-2 and MMP-9 production was significantly higher in bronchoalveolar lavage (3.85- and 11.59-fold, p < 0.001) and airway epithelium (MMP-2 bronchial: 6.33-fold, bronchiolar: 3.57-fold, both p < 0.001; MMP-9 bronchial: 32.55-fold, p < 0.001; bronchiolar: 8.60-fold, p = 0.01) in patients with BOS, but expression in patients without BOS was not different from healthy controls. TIMP expression was similar in patients with and without BOS. Immunostaining confirmed that the airway epithelium was a direct source of MMP-2 and MMP-9 expression in patients with BOS. Conclusion: In patients with BOS, the airway epithelium over-expresses MMPs, even in the absence of acute rejection or infection. Dysregulated epithelial repair may be a key feature of BOS. Â© 2011 International Society for Heart and Lung Transplantation.